E-Siskamling to go to Smart Village: Analysis and design - Saffana Assani; Hermanto (Future Science, 2021)
The implementation of siskamling activities carried out by rotating patrols by residents is a form of system in maintaining community security. In the management of scheduling and delivery of information on the patrol schedule in the siskamling, it is still done manually, so it requires a variety of handicapping tools, a place to store recording tools, inflexible management times, and various means of delivering information. The manual system is also vulnerable to further problems, such as losing patrol schedule records, large record storage areas because records are piling up, and patrol schedule information that does not reach residents because the information media used is not easy to access. This study aims to produce an application that can facilitate the activities of managing the security guard patrol schedule and become a medium for conveying patrol schedule information to residents. The application is also one of the implementations of efforts to become a smart village. The application that will be developed in this research is called E-Siskamling (electronic siskamling). E-Siskamling will be developed using the SDLC (system development live cycle) methodology. This methodology has six development phases, namely feasibility study, investigation, analysis, design, implementation, as well as review and maintenance. This paper will describe the analysis and design of the application, which is part of the iteration phase. The analysis phase is carried out by making a document of the functional and non-functional requirements analysis of the system. For the design includes system design and database design. The system design uses the Unified Modeling Language (UML) and the database design uses a conceptual model design called CDM and a physical model design called PDM. The results of this study are in the form of analysis (functional and non functional analysis documents) and design (UML, CDM, anf PDM) documents. The conclusion in this initial research is that the analysis and design documents are feasible to be used for the next stage, namely application development.